Hubungan pola asuh orang tua dengan status gizi balita - Suryani Suryani; Suri Salmiyati; Putri Arvina Kurniawati (JOURNAL OF Community Health Issues, 2026)
Bacground: Malnutrition in Indonesia remains a major challenge in public health development. Malnutrition in toddlers can cause brain development disorders that affect learning abilities and future productivity. Growth disorders in toddlers are not only influenced by nutritional intake, but also by parenting patterns. Parenting practices play an important role in determining children's nutritional status, as good parenting practices can support optimal nutritional needs and growth and development. Purpose: To determine the relationship between parenting practices and the nutritional status of toddlers. Method: This was a non-experimental quantitative study using a cross-sectional approach. The study population consisted of parents and toddlers who actively attended health center activities at the Melati Kwarasan Nogotirto Health Center in Gamping District, Sleman, with a total of 80 respondents. The sampling technique used total sampling with 80 respondents. The research instruments were a parental care questionnaire and a calibrated digital weighing scale to determine the nutritional status of toddlers. Data analysis was performed using Fisher's Exact Test because the assumptions of the Chi-Square test were not met. Results: Statistical test results using Fisher's Exact Test show a significant relationship between parenting patterns and toddler nutritional status (p = 0.000) with a strong correlation (0.709). Conclusion: There is a significant and strong relationship between parenting patterns and the nutritional status of toddlers.   Keywords: Nutritional Status; Parenting Patterns;  Toddler.   Pendahuluan: Masalah gizi buruk di Indonesia masih menjadi tantangan besar dalam pengembangan kesehatan masyarakat. Kekurangan gizi pada balita dapat menyebabkan gangguan perkembangan otak yang berdampak pada kemampuan belajar serta produktivitas di masa depan. Gangguan pertumbuhan pada balita tidak hanya dipengaruhi oleh asupan nutrisi, tetapi juga oleh pola asuh orang tua. Pola asuh memiliki peran penting dalam menentukan status gizi anak, karena praktik pengasuhan yang baik dapat mendukung pemenuhan kebutuhan gizi dan tumbuh kembang secara optimal. Tujuan: Untuk mengetahui hubungan pola asuh orang tua dengan status gizi balita. Metode: Penelitian kuantitatif non eksperimental menggunakan pendekatan studi cross sectional. Populasi penelitian ini adalah orang tua dan balita yang aktif menghadiri kegiatan posyandu di Posyandu Melati Kwarasan Nogotirto Kecamatan Gamping Sleman dengan jumlah 80 responden. Teknik pengambilan sampel menggunakan total sampling dengan jumlah 80 responden. Instrumen penelitian berupa kuesioner pola asuh orang tua dan timbangan berat badan digital terkalibrasi untuk penentuan status gizi balita. Analisis data dilakukan menggunakan uji Fisher’s Exact Test karena asumsi uji Chi-Square tidak terpenuhi. Hasil: Uji statistik menggunakan Fisher’s Exact Test menunjukan adanya hubungan yang signifikan antara pola asuh orang tua dan status gizi balita (p = 0.000) dengan keeratan hubungan kuat (0.709). Simpulan: Terdapat hubungan yang signifikan dan kuat antara hubungan pola asuh orang tua dengan status gizi balita.   Kata Kunci: Balita; Pola Asuh; Status Gizi.